A protocol for a nationwide multicentre, prospective surveillance cohort and nested-consented cohort to determine the incidence and clinical outcomes of slipped capital femoral epiphysis. (March 2020) - Perry, Daniel C; Arch, Barbara; Appelbe, Duncan; Francis, Priya; Spowart, Catherine; Knight, Marian
Abstract : Aims: Slipped capital femoral epiphysis (SCFE) is one of the most common hip diseases of adolescence that can cause marked disability, yet there is little robust evidence to guide treatment. Fundamental aspects of the disease, such as frequency, are unknown and consequently the desire of clinicians to undertake robust intervention studies is somewhat prohibited by a lack of fundamental knowledge. Methods: The study is an anonymized nationwide comprehensive cohort study with nested consented within the mechanism of the British Orthopaedic Surgery Surveillance (BOSS) Study. All relevant hospitals treating SCFE in England, Scotland, and Wales will contribute anonymized case details. Potential missing cases will be cross-checked against two independent external sources of data (the national administrative data and independent trainee data). Patients will be invited to enrich the data collected by supplementing anonymized case data with patient-reported outcome measures. In line with recommendations of the IDEAL Collaboration, the study will primarily seek to determine incidence, describe case mix and variations in surgical interventions, and explore the relationships between baseline factors (patients and types of interventions) and two-year outcomes. Discussion: This is the first disease to be investigated using the BOSS Study infrastructure. It provides a robust method to determine the disease frequency, and a large unbiased sample of cases from which treatment strategies can be investigated. It may form the basis for definitive robust intervention studies or, where these are demonstrated not to be feasible, this may be the most robust cohort study.